Ética, discursos e corrupção : a produção de sentidos sociais a partir da recepção do quadro 'Cadê o dinheiro que tava aqui?' do Fantástico (Rede Globo) - Chioccola, Fabrizzio Saitta (2019)
Is thesis addresses a discussion on ethics and corruption from consumption and communication field of knowledge, based on a reception study conducted along school teachers, taking as object of discussion the attraction called “Cadê o dinheiro que estava aqui?” (Where is the money that was supposed to be here?), part of TV show “Fantastico”, featured by Rede Globo broadcasting group. As a research problem, we question whether, how and in what extent “Cadê o dinheiro que estava aqui?” contributes to a production of meanings which undermines a notion of ethics and public and collective good, sustaining a neoliberal ethic based on a prevalence of market interest over values as equality, democracy and citizenship. As a primary data collection, we operate two research techniques: a) a stimulated reception study through video exhibition; b) semi-structured questionnaire administering. With regard to the analysis process, with regard to the process of analysis, we opted for the construction of a perspective that combines the theory of mediations (Jesus Martin-Barbero) and the In-depth Hermeneutics (John B. Thompson). We are interested in verifying how the processes of (re) production of meanings about ethics, politics and corruption work, and how it is interwoven with the power structures among teachers, as well as discuss the role of media in this context. Although circumscribed in a limited study, in conclusion, we interpret teachers' statements as having a critical yet paradoxical potential. In some contexts teachers' statements tend to reinforce the rhetoric of neoliberal ethics, although in others, they aim to undermine them, especially in claiming the importance of public affairs in maintaining political and democratic order.